Metabolismo e expressão gênica no fígado durante o período de transição de vacas da raça Holandês e F1 Holandês-Gir - Juliana Guimar?es Laguna (2015)
The aim of the search was to investigate hepatic gene expression of enzymes involved on carbohydrate metabolism (glucose-6- phosphatase (G6PC), peroxisome proliferator-activated receptor alpha (PPARA), glucose transporter (Glut2) and methylmalonyl-CoA mutase (MUT)) and blood concentrations of glucose, non-esterified fatty acid (NEFA) e beta-hydroxybutyric acid (BHBA). For the study, Holsteins cows (n=6) and F1 Holstein x Gir Cows (n=6), under the same pre and postpartum management conditions were used. Liver biopsies samples (to measure G6PC, PPARA, GLUT2 and MUT gene expression) and blood samples (to measure glucose, NEFA and BHBA concentrations), were taken at 15 days pre and at 6, 21, 36, 51 e 66 postpartum. Milk production and milk samples (to evaluate milk composition) were taken at 11°, 25°, 39°, 53° and 67° days of lactation. The experimental design was a completely randomized. Glucose concentration was differed between genetic groups, but it was not differed during transition period. BHBA and NEFA concentrations did not differ between genetic groups. The glucose concentration did not differ during the study. However, concentrations of BHBA and NEFA increased from prepartum to 06 days in milk in the Holstein cows, and to 21 days in milk in the F1 cows. The blood NEFA concentrations reduced from 6 to 51 days and from 21 to 66 days of lactation in Holstein and F1 cows, respectively. The expression of genes G6PC, PPARA and the Glut2 did not differ between genetic groups, but G6PC gene reduced when comparing the pre delivery with 21 and/or 36 days of lactation and 36 vs. 51 and 66 days of lactation. For the MUT gene, mRNA levels differed when compared to the genetic groups and at 21 and 36 days compared with 51 days in milk. This study revealed that specific metabolic pathways are directly related to genetic merit. Starting from these observations, the comparison of differentially expressed genes among animals seems a promising approach to unravel molecular response influenced by blood metabolite concentrations.